A poor diet quality is associated with more gas-related symptoms and a decreased quality of life in French adults. Issue 4 (28th February 2023) - Chaumont, Soline; Quinquis, Laurent; Monnerie, Bénédicte; Six, Chloé; Hébel, Pascale; Chassany, Olivier; Duracinsky, Martin; Le Nevé, Boris
Abstract: This study evaluated the association between dietary patterns, gas-related symptoms (GRS) and their impact on quality of life (QoL) in a representative sample ( n 936) of the French adult population. During the 2018–2019 'Comportements et Consommations Alimentaires en France' survey (Behaviors and Food Consumption in France), online evaluation of GRS in adult participants was performed using the validated Intestinal Gas Questionnaire (IGQ), which captures the perception of GRS and their impact on QoL via six symptom dimensions scores (range 0–100; 100 = worse) and a global score (mean of the sum of the six symptom dimensions scores). Socio-demographics, lifestyle parameters and dietary habits (7-d e-food diary) were also collected online. Quality of diet was determined using the Nutrient-Rich Food 9.3 (NRF9.3) score (range 0–900; 900 = best). Univariate and multivariate linear regression models were applied to identify factors associated with IGQ global score. K-means was used to identify clusters of subjects based on their dietary records. Data from 936 adults who completed both the IGQ and the food diary showed a mean IGQ global score of 11·9 (sd 11·2). Younger age and female sex were associated with a higher IGQ global score. Only 7 % of subjects reported no symptom at all and nearly 30 % of study participants reported a high impact of GRS on their QoL. Two dietary clusters were identified: cluster 1, characterised by a higher consumption of fruits and vegetables, lower sugars intake and higher NRF9.3 score and cluster 2, characterised by higher intake of sugars, lower intake in dietary fibres and lower NRF9.3 score. The IGQ global score was lower in cluster 1 and higher in cluster 2 v. the total sample average ( P < 0·001). The prevalence of GRS in the French adult population is high and is associated with impaired QoL and dietary patterns. A change in food habits towards healthier patterns could help reducing the burden of GRS.